Carbon particles having through holes and mesopores and a method for producing the same

CN122968326APending Publication Date: 2026-10-23TOYOTA JIDOSHA KK +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610512118.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-22
Filing Date
2026-04-17
Publication Date
2026-10-23

Smart Images

  • Figure CN122968326A_ABST
    Figure CN122968326A_ABST
Patent Text Reader

Abstract

The present invention provides a novel carbon particle having a through hole and a mesopore. The carbon particle has a through hole and a mesopore, and the through hole has a radius of 3 times or more the mode diameter of the mesopore.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to carbon particles having through-pores and mesopores, and methods for manufacturing the same. Background Technology

[0002] Patent document 1 describes a catalyst layer for a fuel cell, wherein a catalyst and a polymeric electrolyte are mixed, and the catalyst is formed by supporting catalyst particles on a carbon support with fine pores having a diameter of 4 nm or more and only having openings.

[0003] Non-patent literature 1 describes a method for synthesizing framework-type silica nanoparticles using cubic calcite as a template.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: Japanese Patent Application Publication No. 2010-186678

[0007] Non-patent literature

[0008] Non-patent literature 1: Chika Takai, Masayoshi Fuji, Kyoichi Fujimoto, “Skeletal Silica Nanoparticles Prepared by Control of Reaction Polarity”, Chemistry Letters, Volume 40, Issue 12, 2011, pp. 1346-1348 Summary of the Invention

[0009] The inventors have discovered that carbon particles with unique structures can be manufactured using framework-type silica nanoparticles as described in Non-Patent Document 1. This disclosure provides novel carbon particles with through-pores and mesopores, and a method for manufacturing the same.

[0010] The methods disclosed herein include the following technical solutions.

[0011] [Method 1]

[0012] A type of carbon particle, forming through-pores and mesopores.

[0013] The aforementioned through hole has a radius that is at least three times the modal diameter of the aforementioned mesopore.

[0014] [Method 2]

[0015] The carbon particles according to method 1, wherein the mode diameter of the mesopores is 1 to 7 nm.

[0016] [Method 3]

[0017] The carbon particles according to method 1 or 2 have a radius of 100 to 200 nm.

[0018] [Method 4]

[0019] One method is a method for manufacturing carbon particles with through-pores and mesopores, comprising the following steps in sequence:

[0020] Carbon-coated framework silica nanoparticles were used in a chemical vapor deposition process.

[0021] The first carbon particle is obtained by dissolving and removing the aforementioned framework-type silica nanoparticles.

[0022] The first carbon particles were further coated with carbon using chemical vapor deposition to obtain second carbon particles with through-pores.

[0023] This causes the catalyst metal salt particles to attach to the second carbon particles mentioned above, and

[0024] Mesopores are formed in the second carbon particles through the catalytic reaction of the catalyst metal salt particles.

[0025] [Method 5]

[0026] The method according to method 4 further includes the step of graphitizing the second carbon particles having the above-mentioned mesopores by heat treatment at a temperature above 1400°C. Attached Figure Description

[0027] Figure 1 This is a cross-sectional schematic diagram of the carbon particles in the embodiment.

[0028] Figure 2 This is a flowchart illustrating a method for manufacturing carbon particles according to an embodiment.

[0029] Figure 3 It is a projection image of a three-dimensional reconstructed image of carbon particles obtained by a three-dimensional transmission electron microscope (3D-TEM) observed from the extension direction of the through-pores of the carbon particles.

[0030] Figure 4 These are cross-sectional images of carbon particles obtained through 3D-TEM.

[0031] Symbol Explanation

[0032] 1: Carbon particle; 10: Through-hole; 12: Inner surface of through-hole; 20: Mesopore; 22: Inner surface of mesopore; 32: Outer surface Detailed Implementation

[0033] Hereinafter, embodiments will be described with appropriate reference to the accompanying drawings, but this disclosure is not limited to the embodiments described below. Various modifications, alterations, additions, omissions, and / or combinations of the embodiments described below can be made without departing from the technical scope described in the claims.

[0034] In the accompanying drawings referenced in the following description, the same symbols are sometimes used to denote the same parts or parts with the same function, and repeated descriptions are omitted. For ease of explanation, the dimensional ratios and shapes of the parts in the drawings are sometimes exaggerated and differ from the actual dimensional ratios and shapes.

[0035] In this application, unless otherwise specified, the numerical range represented by the symbol "~" includes the values ​​before and after the symbol "~" as the lower limit and upper limit, respectively. The upper and lower limits described in this application can be used alone or in any combination.

[0036] In this application, unless otherwise specified, "comprising ~" and "containing ~" mean that additional ingredients or elements may be included, including "essentially composed of ~" and "composed of ~". "Essentially composed of ~" means that additional ingredients or elements that do not substantially cause adverse effects may be included. "Composed of ~" means that only the described materials or elements are included, but does not exclude the further inclusion of unavoidable impurities.

[0037] I. Carbon particles

[0038] Figure 1 The carbon particle 1 of the embodiment is shown. A through-hole 10 and a mesopore 20 are formed in the carbon particle 1. At least one through-hole 10 and multiple mesopores 20 may be formed in the carbon particle 1. The surface of the carbon particle 1 may be composed of an inner surface 12 of the through-hole 10, an inner surface 22 of the mesopores 20, and an outer surface 32.

[0039] The through-hole 10 has a radius that is at least three times the modal diameter of the mesopore 20. The modal diameter of the mesopore 20 can be 1–7 nm or 3–6 nm. The radius of the through-hole 10 can be 20–55 nm or 30–50 nm.

[0040] The radius of the through hole 10 can be determined by obtaining a scanning electron microscope (SEM) image of the carbon particle 1, selecting a carbon particle 1 whose extension direction of the through hole 10 is parallel to the depth direction (i.e., the observation direction) of the SEM image, and determining the equivalent circle radius of the through hole 10 of the carbon particle 1.

[0041] The mode diameter of mesopore 20 is determined by obtaining the adsorption isotherm of carbon particle 1 using nitrogen adsorption, analyzing the adsorption isotherm using the BJH method to determine the pore diameter distribution, and then determining the pore diameter with the highest frequency in the pore diameter distribution.

[0042] Carbon particle 1 can have a radius of 100–200 nm or 100–150 nm. The radius of carbon particle 1 can be determined by obtaining an SEM image of carbon particle 1 and calculating the equivalent circle radius of carbon particle 1.

[0043] Carbon particles 1 can be used as a carrier for particles (catalyst particles) that catalyze the electrochemical reactions of fuel cells. Platinum particles can be cited as an example of catalyst particles. Catalyst particles are typically supported on the surface of carbon particles and within mesopores 20 (i.e., the inner surface 22 of the mesopores). Catalyst particles can be supported on carbon particles 1 by any method. Examples of support methods include: (1) contacting carbon particles 1 with a solution containing ions of a catalyst metal element, allowing the ions to adsorb onto carbon particles 1, and then reducing the ions to metal by holding carbon particles 1 in a reducing atmosphere to form catalyst metal particles; (2) immersing carbon particles 1 in a solution containing ions of a catalyst metal element, reducing the ions in the solution to form catalyst metal particles on carbon particles 1; and (3) directly supporting catalyst particles on carbon particles 1 using physical methods. When the catalyst particles are alloy particles, an example of a method for supporting catalyst particles on carbon particles 1 is to support each metal constituting the alloy on carbon particles 1, and then heating carbon particles 1 to form alloy particles.

[0044] The catalyst layer of a fuel cell can be formed using carbon particles 1 carrying catalyst microparticles. In the catalyst layer formed using carbon particles 1, gas can flow not only between the carbon particles 1, but also through the through-holes 10 of the carbon particles 1. Therefore, the catalyst layer formed using carbon particles 1 can have high gas diffusivity.

[0045] In the catalyst layer, the outer surface 32 of the carbon particles 1 and the inner surface 12 of the through-pores can be coated with an ionomer. The ionomer is a proton-conductive polymer electrolyte. Examples of resins that can be used as ionomers include perfluorinated proton exchange resins of fluoroalkyl copolymers having fluoroalkyl ether side chains and perfluoroalkyl side chains. In the catalyst layer of a fuel cell, an electrochemical reaction can occur at the interface of the gas, catalyst particles, and ionomer. In the catalyst layer formed using carbon particles 1, an interface of the three phases—catalyst particles, gas, and ionomer—supported within the mesopores 20 is formed not only near the outer surface 32 of the carbon particles 1 but also near the inner surface 12 of the through-pores. Therefore, the electrochemical reaction occurs more efficiently compared to the case where the through-pores 10 are not formed in the carbon particles 1. Thus, a fuel cell with a catalyst layer formed using carbon particles 1 can have higher output performance.

[0046] II. Methods for manufacturing carbon particles

[0047] Figure 2 The flowchart of the carbon particle manufacturing method according to the embodiment is shown. The carbon particle manufacturing method includes the following steps in sequence: coating framework silica nanoparticles with carbon using chemical vapor deposition (CVD) (S1); dissolving and removing the framework silica nanoparticles to obtain a first carbon particle (S2); further coating the first carbon particle with carbon using CVD to obtain a second carbon particle with through-pores (S3); attaching catalyst metal salt particles to the second carbon particle (S4); forming mesopores in the second carbon particle through a catalytic reaction of the catalyst metal salt particles (S5); and heat-treating the second carbon particle with mesopores to graphitize it (S6). It should be noted that heat-treating the second carbon particle with mesopores to graphitize it (S6) is not necessary and can be an arbitrary step. By the manufacturing method of the embodiment, carbon particles 1 with through-pores 10 and mesopores 20 of the above embodiment can be manufactured (see [reference]). Figure 1 ).

[0048] (1) Carbon coating of framework silica nanoparticles using CVD (S1)

[0049] Framework-type silica nanoparticles can be fabricated using a generally cubic calcite template via the method described in Non-Patent Document 1. Framework-type silica nanoparticles typically have a framework-like lattice shape along the vertices and edges of a cube. In framework-type silica nanoparticles, the interior of the cube is hollow, and pores can be present on each face of the cube. In this application, the cube includes not only a precise cube but also shapes with rounded vertices and / or edges, or shapes with varying lengths on the sides, etc., that are approximately cubic in shape. The carbon source used in the CVD method can be appropriately selected. The conditions of the CVD method (reaction temperature, gas flow rate, reaction time, etc.) can be appropriately set.

[0050] (2) The first carbon particle (S2) is obtained by dissolving and removing the framework silica nanoparticles.

[0051] The framework silica nanoparticles can be dissolved and removed by immersing them in a solution of dissolved silica (e.g., a heated aqueous solution of potassium hydroxide or sodium hydroxide) and stirring for a specified time. The solid components are then recovered from the solution using methods such as vacuum filtration, thereby obtaining the first carbon particles. Multiple immersions in the silica-dissolving solution and recovery of solid components can be performed. This allows for more complete removal of the framework silica nanoparticles.

[0052] (3) Using CVD, the first carbon particles are further coated with carbon to obtain a second carbon particle with through pores (S3).

[0053] The first carbon particle contains voids formed by removing the framework silica nanoparticles. To fill these voids with carbon, the first carbon particle is further coated with carbon using a CVD method. This yields a second carbon particle with interconnected pores. The carbon source used in the CVD method can be appropriately selected. The CVD conditions (reaction temperature, gas flow rate, reaction time, etc.) can be appropriately set.

[0054] (4) Make the catalyst metal salt particles attach to the second carbon particles (S4)

[0055] In the subsequent mesoporous formation step S5, metal salt particles, which function as catalysts for mesoporous formation, are attached to the second carbon particles. Examples of metal salts that function as catalysts for mesoporous formation include nickel nitrate and ferric nitrate. An example of a method for attaching metal salt particles to the second carbon particles is as follows: the second carbon particles are added to an aqueous solution of the metal salt, stirred, the solid components are recovered, and the solution is dried.

[0056] (5) Mesoporous particles (S5) are formed in the second carbon particles through the catalytic reaction of the catalyst metal salt particles.

[0057] To form mesopores through the catalytic reaction of catalyst metal salt particles, a second carbon particle with attached catalyst metal salt particles can be heated in a reducing atmosphere. The resulting mesopores can have a pore diameter equal to the particle size of the catalyst metal salt. Therefore, the mode diameter of the mesopores can be controlled by controlling the mode diameter of the catalyst metal salt.

[0058] The process of attaching catalyst metal salt particles to the second carbon particle (S4) and forming mesopores in the second carbon particle through the catalytic reaction of the catalyst metal salt particles (S5) can be performed more than twice. This increases the volume of the mesopores formed in the second carbon particle.

[0059] (6) The second carbon particle is graphitized by heat treatment (S6)

[0060] Carbon can be graphitized by heat treatment of the second carbon particles that form mesoporous structures. The heat treatment temperature can be above 1400℃.

[0061] Example

[0062] The present disclosure will be described in more detail below through embodiments. However, the scope of the present disclosure is not limited to these embodiments.

[0063] (1) Manufacturing of carbon particles with through-pores and mesopores

[0064] Framework-type silica nanoparticles were prepared according to the method described in Non-Patent Literature 1. Specifically, firstly, carbon dioxide gas was added to a calcium chloride solution to form cubic calcite. After the solution became turbid, dehydroabietic acid (DAA) was added, causing DAA to adsorb onto the calcite. The DAA-adsorbed calcite was then suspended in ethanol to obtain a suspension. Tetraethoxysilane (TEOS), ammonium hydroxide (NH4OH), and distilled water were added to the suspension to initiate a sol-gel reaction. As a result, DAA detached from the vertices and edges (edges) of the cubic calcite, while silicic acid (SiOH) generated from the hydrolysis of TEOS was adsorbed onto the vertices and edges of the calcite. The SiOH-adsorbed calcite was separated from the suspension, suspended in distilled water, and hydrochloric acid (HCl) was added to dissolve and remove the calcite. This yielded framework-type silica nanoparticles.

[0065] Framework silica nanoparticles were coated with carbon using chemical vapor deposition (CVD) with acetylene (C2H2) as the carbon source. The CVD conditions are described below.

[0066] Carrier gas: Ar

[0067] Heating rate: 10℃ / min

[0068] Reaction temperature: 700℃

[0069] C2H2 flow rate: 40 mL / min

[0070] Ar flow rate: 160 mL / min

[0071] Reaction time: 1 hour

[0072] Carbon-coated framework nanoparticles were placed in a 6 mol / L potassium hydroxide (KOH) aqueous solution at 65°C and stirred at 500 rpm for 72 hours. Next, the solid component was recovered by filtration, and the solid component was again placed in a 6 mol / L KOH aqueous solution at 65°C and stirred at 500 rpm for 72 hours. This dissolved and removed the framework nanoparticles. The solid component was then recovered by filtration to obtain carbon particles (carbon particles 1).

[0073] Carbon particles with through-pores (second carbon particles) are obtained by coating the first carbon particles with carbon using C2H2 as the carbon source via CVD. The CVD conditions are described below.

[0074] Carrier gas: Ar

[0075] Heating rate: 10℃ / min

[0076] Reaction temperature: 700℃

[0077] C2H2 flow rate: 40 mL / min

[0078] Ar flow rate: 160 mL / min

[0079] Reaction time: 1.5h

[0080] A nickel(II) nitrate aqueous solution was prepared by dissolving nickel(II) nitrate hexahydrate (Ni(NO3)2·6H2O) in purified water. Second carbon particles were added to the nickel(II) nitrate aqueous solution to suspend it, and the solution was stirred at 300 rpm for 30 minutes. It should be noted that the amount of nickel in the nickel(II) nitrate aqueous solution was 5 parts by weight relative to 100 parts by weight of the second carbon particles added. The solid components were recovered by vacuum filtration, and the solution was dried under reduced pressure at 120°C for 1 hour. This yielded second carbon particles coated with nickel nitrate particles.

[0081] Mesopores are formed by treating the second carbon particles, which are attached with nickel nitrate particles, under the following conditions.

[0082] Reducing gas: hydrogen

[0083] Carrier gas: Ar

[0084] Heating rate: 5℃ / min

[0085] Reaction temperature: 950℃

[0086] Hydrogen flow rate: 40 mL / min

[0087] Ar flow rate: 160 mL / min

[0088] Reaction time: 9 hours

[0089] To increase the volume of the mesopores, the second carbon particles with mesopores were added again to the nickel(II) aqueous solution and suspended, and stirred at 300 rpm for 30 minutes. It should be noted that the amount of nickel in the nickel(II) aqueous solution was 5 parts by weight relative to 100 parts by weight of the second carbon particles added. The solid components were recovered by vacuum filtration and dried under reduced pressure at 120°C for 1 hour.

[0090] Next, the second carbon particle is treated under the following conditions to increase the volume of the mesopores.

[0091] Reducing gas: hydrogen

[0092] Carrier gas: Ar

[0093] Heating rate: 5℃ / min

[0094] Reaction temperature: 950℃

[0095] Hydrogen flow rate: 40 mL / min

[0096] Ar flow rate: 160 mL / min

[0097] Reaction time: 6 hours

[0098] Next, the second carbon particle is graphitized by heating at a temperature above 1400°C. This yields carbon particles with both through-pores and mesopores.

[0099] (2) Structural evaluation

[0100] The manufactured carbon particles were observed using a three-dimensional transmission electron microscope (3D-TEM) to obtain three-dimensional reconstructed images and cross-sectional images. Based on... Figure 3 The projection of the 3D reconstructed image shown confirms that the carbon particles have through-holes in the central portion. According to... Figure 4 The cross-sectional image shown confirms that the carbon particles have multiple mesopores in addition to through-pores.

[0101] Scanning electron microscope (SEM) images of the manufactured carbon particles were obtained. One hundred carbon particles with through-holes extending parallel to the depth direction of the SEM image (i.e., the observation direction) were randomly selected, and the radius (equivalent circle radius) of the through-hole for each carbon particle was determined. The radius of the through-hole was in the range of 30–50 nm.

[0102] In addition, 100 carbon particles were randomly selected from the SEM images of the carbon particles, and the radius (equivalent circle radius) of each carbon particle was calculated. The radius of the carbon particles was in the range of 100–150 nm.

[0103] Adsorption isotherms of carbon particles were obtained using nitrogen adsorption. These isotherms were then analyzed using the BJH method to determine the micropore diameter distribution. The most frequent micropore diameter (i.e., the mode diameter of the mesopores) in the micropore diameter distribution was 5 nm.

Claims

1. A type of carbon particle having through-pores and mesopores, The through hole has a radius that is more than three times the modal diameter of the mesopore.

2. The carbon particles according to claim 1, wherein, The mode diameter of the mesopore is 1–7 nm.

3. The carbon particles according to claim 1 or 2, having a radius of 100 to 200 nm.

4. A method for manufacturing carbon particles having through pores and mesopores, comprising the following steps in sequence: Carbon-coated framework silica nanoparticles were used in a chemical vapor deposition process. The first carbon particle is obtained by dissolving and removing the framework-type silica nanoparticles. The first carbon particles were further coated with carbon using chemical vapor deposition to obtain second carbon particles with through-pores. The catalyst metal salt particles are attached to the second carbon particles, and Mesoporous structures are formed in the second carbon particles through the catalytic reaction of the catalyst metal salt particles.

5. The method according to claim 4, wherein, The method further includes the following step: graphitizing the second carbon particles with the mesopores formed by heat treatment at a temperature above 1400°C.

Citation Information

Patent Citations

  • Catalyst layer for fuel cell

    JP2010186678A